Android-based SAKLAR Application: An Alternative Learning Media for Lorentz Force - Azmar, Azmar; Amalia, Silvia Rahma; Istiani, Nurul (KONSTAN - JURNAL FISIKA DAN PENDIDIKAN FISIKA, 2024)
This study aims to develop and evaluate the feasibility of the Android-based learning application, SAKLAR, as a learning media for Lorentz Force material for junior high school / MTs students. The research uses the Research and Development (R&D) method with the 3D model (define, design, development). At the define stage, needs analysis was conducted through interviews and observations, while the design stage involved designing the application with Canva. At the development stage, the application was developed using Smart Application Creator (SAC) and validated by media and material experts. The validation results showed a feasibility level of 97.1% for the material and 96.2% for the media. A limited trial with 26 students showed that the app improved students' understanding and motivation to learn. This app is expected to be an innovative alternative to technology-based science learning.